(Bio)electroanalytical Applications of Carbon Nanoparticles. Issue 1 (13th November 2015) - Szot, Katarzyna; Opallo, Marcin
Abstract: Most recent application of carbon nanoparticles in electroanalysis are rewieved. After brief introduction on a variety of carbon nanomaterials, the methods of functionalisation or doping of carbon nanoparticles are presented. Next the techniques of their immobilization on the electrode surface are reviewed with special emphasis on layer‐by‐layer deposition and polymer film encapsulation. Then electrochemical properties of carbon nanoparticulate electrodes are presented with the emphasis on their electrocatalytic behavior. Finally the works on bioelectrocatalytic carbon nanoparticulate electrodes modified with enzymes or other biomaterial are reviewed. Abstract :